Modified kernels-alternated error diffusion multipurpose watermarking algorithm for halftone images - NI Jiang-qun1; XIE Zhen1; TANG Lin-na1; HUANG Ji-wu1 (Tongxin xuebao)
A modified kernels-alternated error diffusion（KAEDF） multipurpose watermarking algorithm for halftone images was presented for copyright protection.Firstly,a modified KAEDF（MKAEDF） algorithm for invisible watermarking was developed,which achieved relatively large embedding rate with good visual quality and high robustness.Based on MKAEDF,the modified KAEDF multipurpose（MKAEDFM） watermarking algorithm was further developed for both visible and invisible watermark embedding.The results of simulation indicate that the proposed MKAEDFM watermarking algorithm achieves significant improvements in performance of visual quality and watermark decoding rate.